Radical state how Jihad is winning over democracy in the West - Esman, Abigail R. (Praeger Security International, 2010)
The years since 2001 form the emphasis of the book, focusing on the rising conflict between Western and Muslim cultures. The disclosure of extremist groups, of domestic violence, and even of honor killings in Dutch-Muslim families, has forced powerful changes in the Dutch, and consequently, to some extent, Euro-American, understanding of Islam as it is often practiced within democratic society. And in Holland, perhaps more than in any other Western country, that "clash of civilizations" has reached a point some believe to be insurmountable. Also attempts to elucidate the struggle between those who seek to Islamize Dutch culture, and those who will do whatever necessary, including compromising democracy, to preserve it. Ultimately, the author champions the idea of a supportive, secularized, Enlightenment ideal as it chronicles the rise and fall of a free democracy in a clarion call to America